Identification and initial characterization of novel neural immediate early genes possibly differentially contributing to foraging‐related learning and memory processes in the honeybee. Issue 2 (2nd November 2017) - Ugajin, A.; Uchiyama, H.; Miyata, T.; Sasaki, T.; Yajima, S.; Ono, M.
Abstract: Despite possessing a limited number of neurones compared to vertebrates, honeybees show remarkable learning and memory performance, an example being 'dance communication'. In this phenomenon, foraging honeybees learn the location of a newly discovered food source and transmit the information to nestmates by symbolic abdomen vibrating behaviour, leading to navigation of nestmates to the new food source. As an initial step toward understanding the detailed molecular mechanisms underlying the sophisticated learning and memory performance of the honeybee, we focused on the neural immediate early genes (IEGs), which are specific genes quickly transcribed after neural activity without de novo protein synthesis. Although these have been reported to play an essential role in learning and memory processes in vertebrates, far fewer studies have been performed in insects in this regard. From RNA‐sequencing analysis and subsequent assays, we identified three genes, Src homology 3 ( SH3 ) domain binding kinase, family with sequence similarity 46 and GB47136, as novel neural IEGs in the honeybee. Foragers and/or orientating bees, which fly around their hives to memorize the positional information, showed induced expression of these IEGs in the mushroom body, a higher‐order centre essential for learning and memory, indicating a possible role for the novel IEGs in foraging‐related learning and memory processes in the honeybee.